Effect of microwave irradiation on the electronic structure of ZnO. (August 2015) - Yoshida, Kyohei; Sonobe, Taro; Zen, Heishun; Hachiya, Kan; Okumura, Kensuke; Mishima, Kenta; Inukai, Motoharu; Negm, Hani; Torgasin, Konstantin; Omer, Mohamed; Kinjo, Ryota; Kii, Toshiteru; et al.
Abstract: Modifying the electronic structure may allow a bulk material to efficiently absorb radiation as well as excite and emit atomic plasma. The interaction between microwaves and metal oxides is investigated by analyzing the electronic structure of ZnO with and without microwave (MW) irradiation using absorption, photoluminescence (PL), and PL excitation (PLE) spectroscopies and utilizing an ultraviolet synchrotron light source. MW irradiation lowers the energy of the absorption edge of ZnO producing defects. Additionally, MW irradiation causes a resonantly enhanced change in the intensity and peak shift of the PL band. These phenomena indicate that the defects generated by MW irradiation change the electronic structure of ZnO and the electron transition process. Highlights: The electronic structure of ZnO with and without microwave irradiation was studied. The absorption, PL, and PL excitation spectroscopy were conducted. New defect level was confirmed in ZnO with microwave irradiation. Microwave irradiation changed the electron transition process in ZnO. Microwave irradiation changed the electronic structure of ZnO